Accuracy of Tibial Osteotomy Placement Using 2 Different Tibial Plateau Leveling Osteotomy Jigs. Issue 5 (11th March 2014) - Tan, Christopher J.; Bergh, Mary Sarah; Schembri, Mark A.; Johnson, Kenneth A.
<x xml:space="preserve">Abstract</x> Objective To report the accuracy of osteotomy position in dogs undergoing tibial plateau leveling osteotomy (TPLO) and to evaluate the effect of 2 different TPLO jig and saw systems on tibial osteotomy position. Study Design Retrospective case series. Animals Dogs (n = 124; 134 TPLO). Methods Medical records (2004–2005; 2008–2011) and stifle radiographs of 2 groups of dogs that had TPLO to treat cranial cruciate ligament disease were reviewed. One group had a TPLO performed using an alignment jig system alone (Slocum group), whilst in the other group, an alignment jig system combined with a saw guide (Synthes group) was used. Postoperative radiographs were examined and the distance and direction of the centroid of the osteotomy was compared to the intended osteotomy position. Results The absolute distance of eccentricity (DOE) in the Slocum group (5.6 ± 2.5 mm) was significantly greater than that of the Synthes group (3.4 ± 1.8 mm; P < .01). DOE was caudal and distal in 79% of cases. Conclusions Most tibial osteotomies were centered at a point distal and caudal to the intended osteotomy position. Use of a TPLO system with a saw guide was associated with more accurate placement of the osteotomy and more accurate leveling of the tibial plateau.